Assessing the anthropometric profile of Spanish elite reserve soccer players by playing position over a decade - Vega, J. M.; Gonzalez-Artetxe, A.; Aguinaco, J. A.; Los Arcos, A. (International Journal of Environmental Research and Public Health, 2020)
The aims of this study were to describe the evolution of the anthropometric profile of soccer players over a decade and to compare the anthropometric profiles of players promoted from an elite reserve team to high-level soccer with those players who were not promoted. We examined the body mass, height, body-mass index, and body fat of 98 players enrolled in the reserve team from 2008 to 2018. The players were classified in terms of (a) the highest competitive level they achieved up to the 2019/2020 season (i.e., Spanish 1st-2nd divisions or semi-professional); (b) the period in which they played their last season on the team; and (c) their playing position. Over time, the height of goalkeepers, lateral midfielders, and attackers has increased (effect size = 0.66 ± 1.13) but has decreased in central midfielders (effect size = 0.83). The body fat of defenders has also fallen (effect size = 0.55 ± 0.95). Spanish high-level goalkeepers, lateral midfielders, and attackers were taller than their semi-professional player counterparts (effect size = 1.20 ± 1.98). Body fat did not determine promotion from a reserve team to high-level soccer, but height may be an advantage for several playing positions. The assessment of the anthropometric profile and the application of interventions should be designed according to the playing position.